1997
DOI: 10.1007/s004280050081
|View full text |Cite
|
Sign up to set email alerts
|

Virilizing mature ovarian cystic teratomas

Abstract: Three further cases of mature benign cystic teratomas of the ovary associated with virilization are added to the three previously reported in the literature. They were found in postmenopausal, obese, diabetic women aged 52, 61, and 67 years. The patients presented with hirsutism and voice changes and clitoromegaly was present in one. Testosterone and androstenedione levels were elevated but promptly regressed after removal of the tumours. Histologically, sheets of stromal luteinized cells were found peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…6e8 Most of the virilizing dermoid cysts were identified in postmenopausal women. 5 The youngest patient reported with evidence of virilization associated with a mature teratoma was 25 years old. 9 Therefore, this was an exceedingly rare event to have been identified in an early adolescent with a virilizing type of mature dermoid cyst.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6e8 Most of the virilizing dermoid cysts were identified in postmenopausal women. 5 The youngest patient reported with evidence of virilization associated with a mature teratoma was 25 years old. 9 Therefore, this was an exceedingly rare event to have been identified in an early adolescent with a virilizing type of mature dermoid cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is evidence that virilization can occur after the induction of tissue and not necessarily at a critical time in pubertal development. 5 It is unusual for a mature teratoma to exhibit cells producing active testosterone, and even more rare in the adolescent age group. The disruption of the patient's menstrual cycle for three months prior to her presentation may be explained by rapid growth of the tumor, but a true explanation for this occurrence would only be speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Hyper insulin- emia reinforces testosterone action via insulin effects in the pituitary gland, liver, and ovary (Diamanti-Kandarakis and Papavassiliou 2006). Obesity or diabetes has been previously reported in cases of virilism with MCT (Aiman et al 1977, Lopez-Beltran et al 1997, Rotenberg et al 2009). However, the long-term evaluation of diabetes and insulin resistance in this case could not be performed because of the patient's circumstances.…”
Section: Adrenocorticotropic Hormone Loading Testmentioning
confidence: 91%
“…6 Emoto et al 6 reported on the presence of blood flow in 4 cases with malignant squamous transformation, all showing substantially lower resistive indices (<0.4) suggesting neovascularization. In addition, the coexistence of mature cystic teratomas and hilus cell tumors 7 or Sertoli-Leydig cell tumors 8 in the same ovary has been previously reported in several cases. Nevertheless, in all cases, it was found in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%